c - d; 9 (b, 2015)
Articles on development of villages from Bangladesh.
Includes statistical tables and index.
In Bengali.
Keywords: Villages -- Bangladesh; Rural development -- Bangladesh; Rural development -- Bangladesh -- Statistics; Villages -- Bangladesh -- Statistics; Bangladesh -- Rural conditions; Bangladesh -- Rural conditions -- Statistics